Bukti Tanda Kependudukan Melalui Sistem Elektronik Kartu Tanda Penduduk (E-KTP) di Kabupaten Ponorogo - Dewi Iriani (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2014)
Residence is also defined as a person's domicile, for that the author will provide an explanation of the meaning or understanding of domicile. Domicile is a place where a person is considered always present in terms of exercising his rights and obligations even though he actually resides elsewhere even a legal entity can have a certain domicile, thus domicile can mean a person's residence or the position of a legal entity. To prove a person's domicile or residence, the person must have a KTP. Regulations regarding population are contained in Law No. 23 of 2006 concerning Population Administration, Regent Regulation No. 32 of 2009 concerning Requirements and Procedures for Implementing Population Administration and Civil Registration and Minister of Home Affairs Regulation No. 9 of 2011 concerning Guidelines for Issuing Identity Cards Based on Population Identification Numbers Nationally.